2009
DOI: 10.1080/10401330903014111
|View full text |Cite
|
Sign up to set email alerts
|

Crying: Experiences and Attitudes of Third-Year Medical Students and Interns

Abstract: Crying is common among medical students and interns, especially women. Many consider it unprofessional to cry in front of patients and colleagues. Trainees want more discussions of crying.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 32 publications
3
26
1
Order By: Relevance
“…From these findings it appears that supervision and training with regards to handling the therapist's own emotions in session may have great benefit. Similar to a study of medical professionals, in which trainees reported inadequate discussion of physician crying (Sung et al, 2009), we found that over a quarter (26.9%) of respondents had never discussed their most recent TCIT experience with anyone and only 8% of respondents strongly agreed that they were "prepared for how to handle TCIT." It is notable that, while only one third of respondents sought supervision after their most recent TCIT episode, two thirds of respondents reported speaking with "someone," including peers, personal therapists and significant others.…”
Section: Tcit: Supervision and Training 16supporting
confidence: 80%
See 1 more Smart Citation
“…From these findings it appears that supervision and training with regards to handling the therapist's own emotions in session may have great benefit. Similar to a study of medical professionals, in which trainees reported inadequate discussion of physician crying (Sung et al, 2009), we found that over a quarter (26.9%) of respondents had never discussed their most recent TCIT experience with anyone and only 8% of respondents strongly agreed that they were "prepared for how to handle TCIT." It is notable that, while only one third of respondents sought supervision after their most recent TCIT episode, two thirds of respondents reported speaking with "someone," including peers, personal therapists and significant others.…”
Section: Tcit: Supervision and Training 16supporting
confidence: 80%
“…In a 2009 study of medical trainees, Sung et al (2009) found that the vast majority of medical trainees felt that discussion of physicians' crying was inadequate, and, in a recent study on tears of physicians, Majhail and Warlick (2011) emphasized the importance of supervision and "debriefing" with colleagues with regards to professionals' tears. From these articles, we can see that medical professionals have begun to focus on the importance of discussing physicians' tears in the training process during supervision.…”
mentioning
confidence: 99%
“…Another study found that a large majority of third-year students believed that crying in front of patients or colleagues is unprofessional. 31 Further, although students worry that as their training proceeds they will become less empathetic and more apathetic, 32 and although they want to establish emotional connections with patients, 33 they also are afraid that they will be overwhelmed by their feelings toward patients. 3,34…”
Section: Medical Students' Emotionsmentioning
confidence: 99%
“…35 In the study of attitudes toward crying referred to earlier, attending physicians who cried in front of trainees rarely discussed these displays of emotion; instead, they withdrew physically or simply ignored the tears. 31 Some studies have shown that physicians may lack accuracy in identifying their patients' emotional states 36 -38 ; for example, one study showed that correlations between physician and patient ratings of patient emotions are only small to moderate. 36 Other studies show that physicians do not always even acknowledge patients' emotions.…”
Section: How Physician Role Models Deal With Emotionsmentioning
confidence: 99%
“…Raw emotions in learners, especially tears, are often seen as lack of professionalism. 38 Judgmental negative emotions are not allowed by the formal curriculum, but they are prevalent in the informal curricula which makes the learner resolve that emotions are dangerous and best avoided. 39 The present study showed lower emotion suppression rates in females.…”
Section: Discussionmentioning
confidence: 99%